PESONA DI BALIK KATA: ANALISIS GAYA BAHASA DALAM NOVEL 3726 MDPL KARYA NURWINA SARI DAN IMPLIKASINYA TERHADAP DAYA TARIK PEMBACA. - Risha Nurkhalifah; Sildia Rama Dinda; Mariana Oca; Saptiana Sulastri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The novel 3726 MDPL by Nurwina Sari stands as one of Indonesia's popular literary phenomena of 2024, having set a sales record of over 40,000 copies within three days of its release. This study aims to describe the variety of language styles employed in the novel and to analyze their influence on reader appeal. A descriptive qualitative method with a stylistic approach was applied, drawing on the theoretical frameworks of Keraf (2016) and Nurgiyantoro (2017). Data were collected through careful reading and note-taking techniques applied to narrative excerpts, dialogues, and descriptions containing figurative language. The analysis reveals five dominant language styles in 3726 MDPL: simile, metaphor, personification, hyperbole, and metonymy. The novel's distinctiveness lies in its blending of casual, colloquial dialogue with reflective, poetic expressions, creating a stylistic dualism that is simultaneously accessible and aesthetically rich. These language styles are found to enhance reader appeal through four primary mechanisms: emotional resonance, narrative immersion, high readability, and strong quotability in the social media era. The study concludes that the deliberate and precise selection of language style is a key factor in bridging literary value and market appeal in contemporary popular fiction.